Role of TRPV1 in neuroendocrine regulation: a potential target against obesity? - Wang, Jiexin; Liu, Maohui; Wen, Lingmiao; Xing, Pengfei; Chen, Jiawei; Xia, Xiuwen; Ding, WeiJun (Frontiers in Immunology, 2025)
Obesity is a common metabolic syndrome in which an imbalance between energy intake and consumption is the main cause of excessive accumulation of body fat. The increasing prevalence of obesity and its associated complications poses significant challenges to public health. Activation of the transient receptor potential vanilloid subtype 1 (TRPV1) cascade plays a key role in lipid metabolism and energy intake. TRPV1 is expressed across the central nervous system and peripheral organs is involved in the regulation of hormone secretion, appetite and mitochondrial function, and is recognized as one of the key targets for preventing obesity. The current treatments for obesity exhibit limited efficacy and are associated with numerous side effects. Targeting TRPV1 represents a potentially effective approach for managing obesity. In this work, by combining the recent mechanism of the role of TRPV1 in neuroendocrine regulation, we hope to provide novel approaches to block or even reverse the development of obesity.